2018
DOI: 10.1038/s41416-018-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Neoepitope targets of tumour-infiltrating lymphocytes from patients with pancreatic cancer

Abstract: BackgroundPancreatic cancer exhibits a poor prognosis and often presents with metastasis at diagnosis. Immunotherapeutic approaches targeting private cancer mutations (neoantigens) are a clinically viable option to improve clinical outcomes.Methods3/40 TIL lines (PanTT26, PanTT39, PanTT77) were more closely examined for neoantigen recognition. Whole-exome sequencing was performed to identify non-synonymous somatic mutations. Mutant peptides were synthesised and assessed for antigen-specific IFN-γ production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Furthermore, the high stromal density and absence of angiogenesis dampen the infiltration of infused cells, and the suppressive TME also inactivates infiltrating cells. Promisingly, substantial progress has been made regarding PDAC TILs in recent years [135][136][137]. These results exploited potential tools to obtain multiple tumourspecific colonies and even a single TIL colony specific for endogenous tumour cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the high stromal density and absence of angiogenesis dampen the infiltration of infused cells, and the suppressive TME also inactivates infiltrating cells. Promisingly, substantial progress has been made regarding PDAC TILs in recent years [135][136][137]. These results exploited potential tools to obtain multiple tumourspecific colonies and even a single TIL colony specific for endogenous tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, they reported that peripheral blood mononuclear cells (PBMCs) as well as TILs could be used to screen neoantigens. These results pave the way for highly specific and personalized ACT [137] since targeting personalized mutations has been demonstrated to be a durable approach for the treatment of metastatic solid tumours with a relatively low mutation burden [138].…”
Section: Stromnes Et Al Conducted Ground-breaking Research Inmentioning
confidence: 91%
“…Neoantigen-specific T cells can be identified in patients not only with melanoma, but also with epithelial cancers, such as lung cancer [119,120], gastrointestinal cancer [121][122][123], ovarian cancer [124][125][126], breast cancer [127] and pancreatic cancer [128]. Case reports have demonstrated that treatment of the gastrointestinal and breast cancer patients with a T cell population highly enriched in neoepitope-specific T cells caused tumour regression [121,123,127].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%
“…Many attempts have been made to find new antigens and use them for immunotherapy in various cancer types, 55 including PDAC. 55 Neoantigens, which have high tumor specificity, exhibit distinctive advantages when used in CAR-T therapy. In addition, tumors from different patients may express different neoantigens, and neoantigen-guided CAR-T therapy will conform better to the requirements of precision medicine.…”
Section: Car-t Therapymentioning
confidence: 99%